Общественная благотворительность и попечительство в пенитенциарных учреждениях Российской империи - Щукин, Владимир Владимирович; Щукін, Володимир Володимирович; Shhukin, Vladimir (My University, 2012)
The article is devoted about the activities of the Trusteeship of the Prison Society which forced in the Russian Empire in the nineteenth century for 80 years and cares about improving the conditions of detention in prisons.
Щукин В. В. Общественная благотворительность и попечительство в пенитенциарных учреждениях Российской империи / В. В. Щукин // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 456-463.
Keywords: благотворительность; попечительство; пенитенциарные учреждения; Российская империя; благодійність; піклування; пенітенціарні заклади; Російська імперія; charity; welfare; prisons; Russian Empire